A classification system for youth outpatient behavioral health services billed to medicaid - Rodríguez, Gabriela M.; Pederson, Casey A.; Garcia, Dainelys; Schwartz, Katherine; Brown, Steven A.; Aalsma, Matthew C. (Frontiers in Health Services, 2024)
Rates of youth behavioral health concerns have been steadily rising. Administrative data can be used to study behavioral health service utilization among youth, but current methods that rely on identifying an associated behavioral health diagnosis or provider specialty are limited. We reviewed all procedure codes billed to Medicaid for youth in one U.S. county over a 10-year period. We identified 158 outpatient behavioral health procedure codes and classified them according to service type. This classification system can be used by health services researchers to better characterize youth behavioral health service utilization.